In the Realm of Reason: Al-Fârâbî's Logic and Language Paradigm - Rahman, Fadhlur; Kholid, Mohammad (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Al-Farabi, an Islamic philosopher, focused on the correlation between logic and language, particularly regarding the process of reasoning. He classified logic into eight components, which align with the eight books of the Aristotelian Organon, and delineated logic as a system of rules governing thought. He asserted that the objectives of logic are to govern and direct reason towards correct thinking, establish measures to prevent mistakes and assign significance to comprehensible acknowledgments of error. As Aristotle's logic encompasses a set of methods aimed at effectively persuading others, regulating debate, uncovering truths, and attaining certainty, Al-Farabi regarded the formal rules of logic as heuristics (mental shortcuts that help people make quick decisions), rather than as laws of a scientific theory. He analogized logic to tools like rulers and compasses, which are employed to guarantee precision when measuring physical objects that are susceptible to errors. Further, he characterized it as a science based on rules that regulate the mental processes involved in comprehending abstract concepts served as the basis for Ibn Sina's subsequent enhancements. Al-Farabi's philosophy of logic and language is expounded in his writings, and he deserves to be regarded on par with Plato, Aristotle, Kant, and Hegel in this aspect of his work.